Scientific Reasoning in Biology – the Impact of Domain-General and Domain-Specific Concepts on Children’s Observation Competency - Klemm, Janina; Flores, Pamela; Sodian, Beate; Neuhaus, Birgit J. (Frontiers in Psychology, 2020)
Research on the development of scientific reasoning has put the main focus on children’s experimentation skills, in particular on the control-of-variables strategy. However, there are more scientific methods than just experimentation. Observation is a scientific method which is especially relevant for inquiry in biology, but also an important prerequisite for other methods. Previous research has shown that the quality of observations depends on specific knowledge in the domain. We argue that observation competency shares the domain-general ability to differentiate hypotheses from evidence with other scientific methods. The present study investigates the relations of both domain-general scientific thinking and domain-specific knowledge with observation competency in grade K children. We tested relations between observation competency, domain-general scientific reasoning, domain-specific knowledge and language abilities of 75 children (age 4;9 to 6;7). Both scientific reasoning and domain-specific knowledge proved to be significant predictors of observation competency, explaining 35% of the variance. In a mediation analysis, we found a significant indirect effect of language via these two predictors. Thus, the present results indicate that observation skills require not only domain-specific knowledge but also domain-general scientific reasoning abilities.